Financial Distress During the Covid-19 Pandemic:Altman and Springate Model Prediction - Herdiansah Andri; Ekayana Sangkasari Paranita (The Graduate School of Sahid University, 2023)
The purpose of this research is to analyze the prediction of financial distress of retail trade companies. This research chose to use the Altman and Springate Models since both of them are the most accurate and conservative models to predict. The calculation of the Altman and Springate Score is based on an equation formula for data in the period before and during the Covid-19 pandemic. The Altman’s Score is grouped in the Safe Zone, Grey Area, and Financial Distress; while the Springate’s Score is grouped in the Safe Zone and Financial Distress categories. Altman Model Analysis stated that most of the companies experienced decreased scores, the company's financial performance during Covid-19 pandemic was predicted financial distress and belonged to the Grey Zone category than before Covid-19 pandemic. Springate Model Analysis states that all companies have decreased scores, and the company's financial performance during Covid-19 pandemic is predicted financial distress than before Covid-19 pandemic. Springate Model revealed a more conservative indicator, but both models stated there are still several companies in the Safe Zone category to continue their business. The originality of this research is focused on the retail trade companies as the most affected industry by Covid-19 pandemic. In addition, this research analyzes financial distress based on the Altman Z-Score and Springate Model as the most powerful model to predict.